HERDING BIAS INVESTOR MASA NEW NORMAL PANDEMI COVID-19 - Wida Fadhlia; Nurhalis Nurhalis; Linda Linda; Syarifah Rahmawati Al Haddad (Jurnal Akuntansi Trisakti, 2023)
This study examines the determinants of herding bias in investors in Indonesia during the Covid-19 New Normal period. This study was conducted for six months to survey the behavior of 232 investors with a single investor identification in the Indonesian capital market who were haphazardly selected to test the herding bias model. The results of Confirmatory Factor Analysis show that reputational factors, social proof, lack of awareness, volatility in global markets, underconfidence, optimism, bandwagon effect, and speculation are the determinants of investor herding bias in Indonesia. The results of this study also prove that the reputation factor is the dominant factor determining herding behavior, where investors will follow the behavior of their community to maintain their reputation. The second factor that contributes highly to determining herding bias is social proof, which means that Indonesian investors consider social roles in the decision-making process. We hope the results of this study can provide researchers and practitioners with a better understanding of herding behavior which is part of the theory of financial behavior.